Doing research in fashion and dress : an introduction to qualitative methods - Kawamura, Yuniya, 1963-; Bloomsbury Professional (Firm) (London ; New York : Bloomsbury Visual Arts, 2020)
"Whether you're investigating fashion as a material object, an abstract idea, a social phenomenon, or a commercial system, qualitative techniques can further your understanding of almost any research topic. Doing Research in Fashion and Dress begins by guiding you through a brief history of fashion studies, and the debates surrounding it, before introducing key qualitative methodological approaches, including ethnography, semiology, and object-based research. Detailed case studies demonstrate how each methodology is used in practice. These case studies include Japanese subcultures, fashion photography blogs and semiotic studies of fashion magazine shoots and advertisements. This second edition also features a new chapter on internet sources and online ethnography, reflecting the adoption of social media tools not only by industry practitioners but also by academics. By contextualizing history, theory and practice Doing Research in Fashion and Dress offers: -A systematic examination of qualitative research methods in fashion studies in social sciences. -A practical guide to anyone wishing to conduct fashion research in academia or in the business world. -An accessible grounding in contemporary fashion studies literature"--
"First published in Great Britain by Berg 2011"--T.p. verso.
Includes bibliographical references and index.
Keywords: Fashion -- Research; Qualitative research; Fashion -- Research -- Case studies; Qualitative research -- Case studies